Silver nanoparticles from Arbutus unedo extract: Green synthesis, antibacterial activity, and TMPRSS2 enzyme inhibition - Tavukcuoglu, Ozlem; Ciftci, Fatih; Duygulu, Nilufer Evcimen; Coban, Muhammedul Emin; Misirli, Duygu; Elmastas, Mahfuz (ELSEVIER, 2026)
This study examines the green synthesis and characterization of silver nanoparticles (AgNPs) derived from extracts of Arbutus unedo leaves (AUL) and fruits (AUF), with a specific emphasis on their inhibitory effects on Transmembrane Serine Protease 2 (TMPRSS2), an enzyme that facilitates viral entry, including SARS-CoV-2. The phenolic composition of the extracts was analyzed via high-performance liquid chromatography (HPLC). AgNPs were characterized using ultraviolet-visible (UV-Vis) spectroscopy, dynamic light scattering (DLS), Fourier-transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), and transmission electron microscopy (TEM). AgNPs displayed a face-centered cubic (fcc) crystalline structure with grain sizes of similar to 13.21 nm for AUL_AgNPs and 14.85 nm for AUF_AgNPs. Antibacterial activity was evaluated against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The inhibition zones for E. coli were 23.41 mm and 20.70 mm, for S. aureus, 23.70 mm, and 21.68 mm for AUF_AgNPs and AUL_AgNPs, respectively. Cytotoxicity was assessed using direct and indirect XTT assays on L929 fibroblast cells. AUL_AgNPs and AUF_AgNPs showed high viability (similar to 125% and 120%) at 100 mu g/mL in direct contact, with extracts around 100%, indicating low toxicity. In indirect assays, viability decreased with dose, with AUL_AgNPs at similar to 80% and AUF_AgNPs at similar to 65% at 100 mu g/mL. TMPRSS2 inhibition assays demonstrated that AUL_AgNPs achieved approximately 69% inhibition at 100 mu g/mL. Although the AgNPs were less effective than the reference inhibitor Camostat (50 nM), they exhibited non-covalent interactions with TMPRSS2. This suggests their potential as multifunctional therapeutic agents with antimicrobial and enzyme-inhibitory activity.
Keywords: Silver nanoparticles; Green synthesis; Arbutus unedo; TMPRSS2 inhibition; SARS-CoV-2; OFFICINALIS; PLANTS; Food Science & Technology